2013
DOI: 10.1371/journal.pone.0065308
|View full text |Cite
|
Sign up to set email alerts
|

13-Methyltetradecanoic Acid Exhibits Anti-Tumor Activity on T-Cell Lymphomas In Vitro and In Vivo by Down-Regulating p-AKT and Activating Caspase-3

Abstract: 13-Methyltetradecanoic acid (13-MTD), a saturated branched-chain fatty acid purified from soy fermentation products, induces apoptosis in human cancer cells. We investigated the inhibitory effects and mechanism of action of 13-MTD on T-cell non-Hodgkin’s lymphoma (T-NHL) cell lines both in vitro and in vivo. Growth inhibition in response to 13-MTD was evaluated by the cell counting kit-8 (CCK-8) assay in three T-NHL cell lines (Jurkat, Hut78, EL4 cells). Flow cytometry analyses were used to monitor the cell cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 42 publications
2
39
0
2
Order By: Relevance
“…via Akt) and induces ER stress and/or an apoptotic response [15–17]. In particular, incubation of cells with BCFA also causes apoptosis [18, 19]. In these studies, non-esterified BCFA were solubilized by non-ionic surfactants (Tween 80) and therefore were present as unbound fatty acids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…via Akt) and induces ER stress and/or an apoptotic response [15–17]. In particular, incubation of cells with BCFA also causes apoptosis [18, 19]. In these studies, non-esterified BCFA were solubilized by non-ionic surfactants (Tween 80) and therefore were present as unbound fatty acids.…”
Section: Discussionmentioning
confidence: 99%
“…The high level of BCFA incorporation in our experiments, and apparently low toxicity in vitro suggests these cells are indeed highly tolerant and may well have evolved specific uses for BCFA at uniquely in vivo high exposures in the late term fetal gut. In contrast, iso -15:0 induces apoptosis in various human cancer cells with IC 50 ranging from 0.04 mM to 0.16 mM, including breast cancer (MCF-7), T-cell lymphomas (Jurkat and Hut78 cells), prostate cancer (E4 and DU145 cells), and hepatocarcinoma (NCI-H1688 cells)[18, 19]. In these studies, iso -15:0 was not solubilized by albumin, raising the possibility that the free fatty acid concentration was relatively high.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it was reported that iso and anteiso BCFA show antitumoral activity in human cancer cells [19], [20] and also reduce the incidence of necrotizing enterocolitis, a devastating intestinal disease affecting premature infants [21]. However, as far as we know, there is no information available about the potential health effects of the non-terminal mono- and di-methyl BCFA.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of T-cell leukemia/lymphoma accounts for 30% of all non-Hodgkin lymphomas in Asia [2]. T-cell leukemia/lymphoma has a poor prognosis and is more aggressive than B-cell lymphoma.…”
Section: Introductionmentioning
confidence: 99%